2012
DOI: 10.1002/pd.3865
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound estimated fetal weight slightly below the median is associated with increased risk of spontaneous preterm birth

Abstract: In asymptomatic women between 28 and 36 weeks of gestation, an EFW lower than 0.90 MoM increases by 4.6 times the risk of spontaneous preterm birth, and the risk increases proportionally to the degree of weight reduction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 20 publications
(57 reference statements)
1
9
0
Order By: Relevance
“…In addition, this study observed a negative association between maternal NO 2 exposure levels and FL and EFW in the second trimester, which has not been reported before. Regarding the possible consequences, it has been reported that low prenatal EFW and short prenatal FL are associated with adverse perinatal outcomes, such as preterm birth and neonatal intensive care unit admissions 26 27. This new finding may be partially driven by a high prenatal NO 2 exposure level.…”
Section: Discussionmentioning
confidence: 96%
“…In addition, this study observed a negative association between maternal NO 2 exposure levels and FL and EFW in the second trimester, which has not been reported before. Regarding the possible consequences, it has been reported that low prenatal EFW and short prenatal FL are associated with adverse perinatal outcomes, such as preterm birth and neonatal intensive care unit admissions 26 27. This new finding may be partially driven by a high prenatal NO 2 exposure level.…”
Section: Discussionmentioning
confidence: 96%
“…Another study involving 3653 uncomplicated preg nant women, showed that the odds ratio for preterm delivery increased even with slight deviation of UEFW below the median and with further deviation, the likeli hood for preterm delivery increased drastically. 1 A systematic review regarding the prediction of spon taneous preterm birth put forward the proposal that a more accurate prediction may be possible by combining several tests, including cervical length prediction and fetal fibronectin measurement in cervicovaginal fluid. 4 But such tests deal with only one aspect of preterm labor, i.e.…”
Section: Discussionmentioning
confidence: 99%
“…Filiberto M Severi and coworkers concluded that ultrasound estimated fetal weight (UEFW) slightly below the median also is asso ciated with increased risk of spontaneous preterm birth. 1 This study was con ducted to find out the association of UEFW between 10th and 50th centile, as well as weight below the median in early third trimester (28-34 weeks) and the risk of spontaneous preterm delivery.…”
Section: Introductionmentioning
confidence: 99%
“…This hypothesis is supported by clinical and experimental evidence; for example, pregnant women at high altitude (>4,000 meters above sea level) have triple chance of premature delivery than women living at sea level (12 versus 4%) [14]. Clinical conditions that are a reflection of placental ischemia, such as preeclampsia and fetal growth restriction, are frequently associated with premature onset of labor [5, 15]. The anatomical-clinical correlation between preterm birth and placental morphology (histology) indicating uteroplacental ischemia has also been demonstrated [7, 1618].…”
Section: Uteroplacental Ischemia and Preterm Birthmentioning
confidence: 99%